Evaluation of xylose-utilising yeasts for xylitol production from second generation ethanol vinasse and effect of agitation intensity in flask-scale xylitol production - Sreyden Hor,; Mallika Boonmee Kongkeitkajorn,; Alissara Reungsang, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aimed to select a yeast strain that effectively utilises xylose to produce xylitol from the vinasse of ethanol broth obtained from the fermentation of sugarcane bagasse hydrolysate. Eleven strains of xylose-fermenting yeasts were evaluated for their abilities to utilise xylose and produce xylitol. Two strains that showed outstanding performance in the semi-defined xylose medium were selected for further testing with a vinasse medium. Candida guilliermondii TISTR 5068 showed a superior xylitol production of 7.03 ± 0.08 g/L with the xylitol yield of 0.70 g/ gxylose when cultured in bagasse-based ethanol vinasse. The strain was further tested for its xylitol production performance when cultured at four different agitation intensities. Excessive agitation resulted in a rapid xylitol production rate but caused xylitol consumption once the xylose was depleted. Moderate agitation resulted in the highest xylitol yield of 0.79 g/gxylose. The results of this study have provided important information for the development of the xylitol production process using waste streams from cellulosic ethanol production.